The role of social resources in formation of wealth in the decentralization and industry 4.0 processes - Vishnevsky, O. (Економічний вісник Донбасу, 2016)
The paper analyzes the role of social resources in the formation wealth of the state and regions. The need to remove the physical and administrative barriers to the capitalization of social resources taking into account the decentralization process and the industry 4.0. У роботі проаналізовано роль соціальних ресурсів у формуванні багатства держави та регіонів, а також доведено необхідність зняття фізичних та адміністративних бар’єрів для капіталізації соціальних ресурсів з урахуванням процесів децентралізації та індустрії 4.0. В работе проанализирована роль социальных ресурсов в формировании богатства государства и регионов, а также доказана необходимость устранения физических и административных барьеров для капитализации социальных ресурсов с учетом процессов децентрализации и индустрии 4.0.